Estimation of planetary boundary layer height using Suomi NPP-CrIS soundings. Issue 7 (2nd July 2016) - Prijith, S. S.; Rao, P. V. N.; Sujatha, P.; Dadhwal, V. K.
ABSTRACT: The study estimates planetary boundary layer height (PBLH) using temperature and humidity profiles from Cross-Track Infrared Sounder (CrIS) onboard Suomi National Polar-Orbiting Operational Environmental Satellite System Preparatory Project (SNPP). PBLH is estimated using six different methods and also using an integrated approach. PBLH estimated from SNNP-CrIS soundings by the integrated approach is compared with the PBLH values estimated using atmospheric profiles from radiosonde ascents and Constellation Observing System for Meteorology Ionosphere and Climate-radio occultation (COSMIC-RO) measurements. Analysis shows reasonable agreement of PBLH values from SNPP-CrIS soundings with those from radiosonde measurements and COSMIC-RO retrievals, thus revealing the capability of atmospheric profiles from SNNP-CrIS for the characterization of planetary boundary layer (PBL) with excellent spatial resolution and coverage. PBLH from SNNP-CrIS soundings are observed to be overestimated by around 336 m compared to the estimates from radiosonde ascends and is partly attributed to the difference in time of observations and coarse vertical resolution of the SNPP-CrIS-derived profiles. Compared to the estimates from SNPP-CrIS soundings, PBLH values from COSMIC-RO profiles are overestimated by around 596 m. Estimates from SNPP-CrIS soundings, through the integrated approach, are further used to examine the spatial and seasonal variations of PBLH over the Indian landmass. PBLH is observed highest in pre-monsoon and lowest in winter over most of the regions. Due to rainfall and associated changes in lower atmosphere and surface characteristics, PBLH is observed shallow during monsoon.